The Evaluation of Traffic Noise on Different Road Slopes (Case Study of Padaleunyi Toll Road) - Rahmasari Suhartono, Bunga
One of the effect of toll road construction is causing the raising of residential area growth. However, this bring some negative impacts to the residents as well, such as traffic-induced noise. The case of this study is located in Padaleunyi Toll Road, which consists of several uphills and downhills. Thus, this study will evaluate noises regarding of traffic characteristics on different road slopes by proposing a mathematical model that may help to predict traffic noises. It is also provide some feasible recommendations according to Pt-T-16-2005-B to mitigate toll road noises. The result shows that the noise levels are 74 dB(A) for level roads and 77 dB(A) for uphill roads. Both of these noise levels have exceeded the noise threshold allowed for residential areas which is 55 dB(A) according to Kep-48/MENLH/11/1996. The predicted mathematical model consists of two dependent variables and three independent variables. The two dependent variables are differentiated by distance of measurement, that are Y1 (distance of measurement of 18 m) and Y2 (distance of measurement of 23 m). Whilst, the three independent variables consist of X1 (vehicle flow), X2 (percentage of HV > 2as), and X3 (mean speed of HV > 2as). The following results are the predicted mathematical models: for level roads (0% slope): Y1 = 76.251 + 0.0002 X1 + 0.034 X2 - 0.045 X3, Y2 = 72.869 + 0.0001 X1 + 0.041 X2 - 0.032 X3, for uphill roads (4% slope): Y1 = 79.960 + 0.0002 X1 + 0.038 X2 - 0.066 X3, Y2 = 76.662 + 0.0001 X1 + 0.044 X2 - 0.079 X3. The model shows that %HV>2as (X2) and mean speed of HV>2as (X3) are the most influential factors of noise on uphill roads. It is evidenced by higher regression coefficient value in uphill roads compared to level roads. Mitigations for noise level in the location of study can be achieved by raising the height of right of way fences made of precast concrete panel walls by 4 m to reduce the noise by 19 dB(A), and planting pringgodani bamboo to reduce the noise by 4.9 dB(A). Thus, the total reduction resulting from the two noise barriers is 23.9 dB (A). Consequently, the noise felt by residents around the toll road is reduced to 50.1 dB(A) in level areas, and 53.1 dB(A) in uphill areas. Other types of noise barriers that can be researched are Photovoltaic Noise Barries which have the function of reducing noise and producing renewable energy simultaneously.